2018
DOI: 10.1002/ijc.31744
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid‐derived suppressor cells: Roles in the tumor microenvironment and tumor radiotherapy

Abstract: Cancer progression is closely related to the tumor microenvironment in which the tumor exists, including surrounding blood vessels, immune cells, fibroblasts, bone marrow-derived inflammatory cells, signaling molecules and the extracellular matrix. Tumors can influence the microenvironment by releasing extracellular signals, promoting tumor angiogenesis and inducing peripheral immune tolerance, while the immune cells in the microenvironment can impact the growth and evolution of cancerous cells. One of major c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(55 citation statements)
references
References 141 publications
(146 reference statements)
2
53
0
Order By: Relevance
“…We further found that the expression of Arginase‐1 (Arg1), a pro‐healing marker, was enhanced when macrophages were cultured on laminin, Matrigel and vitronectin compared to the other ECMs . Interestingly, these ECMs have been associated with tumors, which are often laden with protective M2‐like macrophages, often referred to as myeloid suppressor cells . Taken together, these results suggest that ECM coatings have minimal impact on inflammatory activation, but may play a more significant role in polarization toward a pro‐healing phenotype.…”
Section: Regulation Of Macrophages By Biophysical Cuesmentioning
confidence: 74%
“…We further found that the expression of Arginase‐1 (Arg1), a pro‐healing marker, was enhanced when macrophages were cultured on laminin, Matrigel and vitronectin compared to the other ECMs . Interestingly, these ECMs have been associated with tumors, which are often laden with protective M2‐like macrophages, often referred to as myeloid suppressor cells . Taken together, these results suggest that ECM coatings have minimal impact on inflammatory activation, but may play a more significant role in polarization toward a pro‐healing phenotype.…”
Section: Regulation Of Macrophages By Biophysical Cuesmentioning
confidence: 74%
“…A recent study showed that Notch1 expression not only inhibited the infiltration of cytotoxic CD8 + T cells and NK cells in melanoma, but also reduced the release of IFN‐γ in the tumour tissue. Additionally, it enhanced the inhibition of T cell proliferation and activation, and lead to a significant increase of MDSCs in the tumour microenvironment . Prior to this report Peng et al demonstrated that MDSCs could induce phosphorylation of STAT3 (Figure ),a vital oncogenic mediator and lead to its prolonged activation by inducing nitric oxide (NO) mediated NOTCH signalling …”
Section: Notch Mediated Immune Surveillance Through Cancer Stem Cellsmentioning
confidence: 97%
“…In addition to its important roles in CSCs, Notch signalling is also involved in EMT to promote cancer cell acquisition of a stem‐like phenotype and drug resistance . Notch signalling has also merged crucial player in regulation of cytokine secretion by T cells and in immune homeostasis . For instance, prostate cancer cells undergoing EMT displayed stem‐like cell features characterized by increased expression of Notch 1 and other pluripotent genes such as Sox2, Nanog, Oct4 and Lin28 …”
Section: Notch Mediated Immune Surveillance Through Cancer Stem Cellsmentioning
confidence: 99%
“…MDSCs are a further object of study, and several preclinical models have been designed to understand how to interfere with these immature myeloid cells. Phase I and II trials are ongoing, however to date, no studies have been completed in HCC patients. A phase I study (NCT03665129) recruiting non‐small cell lung cancer and HCC patients is based on the combination of anti‐C5AR and anti‐PDL1.…”
Section: Introductionmentioning
confidence: 99%
“…TA B L E 1 Immunotherapeutic trials for HCC Hepatocellular carcinoma; α-, anti-; ORR, overall response rate; na, not available; RR, response rate; ns, not significant.to interfere with these immature myeloid cells. Phase I and II trials are ongoing,136 however to date, no studies have been completed in HCC patients. A phase I study (NCT03665129) recruiting non-small cell lung cancer and HCC patients is based on the combination of anti-C5AR and anti-PDL1.Inhibition of Treg-induced suppression 53 may be effective in res-cuing anti-tumour immune response.…”
mentioning
confidence: 99%